PENGARUH PENGGUNAAN KARET COMPO CREPE DENGAN FILLER CARBON BLACK TERHADAP KARAKTERISTIK FISIS VULKANISAT KARET UNTUK PRODUK KARET BANTALAN DERMAGA - suwarno, yuli (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2024)
Marine Rubber fenders are rubber products that function to absorb and transmit impact energy originating from ships to the dock structure and protect the dock from impacts from docked ships. Locally produced natural rubber-based marine rubber fenders often experiences quality problems in terms of resistance to wear and permanent compression. This research aims to study the effect of using compo crepe rubber with carbon black filler in making natural rubber vulcanisate for marine rubber fender products. In this research, carbon black filler was added with varying amounts of 60,65,70,75 and 80 phr. The experiment began with making a rubber compound on a laboratory scale. The rubber compound obtained was then molded for test samples to characterize the mechanical properties of vulcanized rubber for marine rubber fender. Test parameters refer to SNI 06-3568-2006. The combination of compo crepe natural rubber with all variations of carbon black filler are able to produce physical characteristic values of hardness, breaking stress, elongation at break, tear resistance that meet SNI standards. The compression value still meets SNI standards with carbon black 70 phr. Aging has a significant influence on the physical characteristics of elongation at break with a decrease in values that exceed SNI standards. Natural rubber compo crepe can be used as a raw material for marine rubber fender with the addition of a certain amount of carbon black.Keywords : marine rubber fender, compo crepe, carbon black, mechanical properties